1998
DOI: 10.2511/rpsd.23.1.69
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Supported Work versus Center-Based Program Services on Selected Outcomes for Individuals with Multiple Severe Disabilities

Abstract: The effects of supported work versus center-based program services were evaluated with four individuals who have multiple severe disabilities. Each week the individuals participated in supported work placements in a publishing company and in a center-based program within an adult education department at a residential center. Systematic observations were conducted in multielement fashion of the degree to which the individuals displayed alert and active behavior, were involved in purposeful activity, and exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Reid, Green, and Parsons (1998) used indices of happiness to evaluate preference of the type and location of various work activities. The authors observed indices of happiness of four individuals with PMD in center-based and supported work (i.e., community) experiences.…”
Section: Evaluating Activities Using Indices Of Happinessmentioning
confidence: 99%
“…Reid, Green, and Parsons (1998) used indices of happiness to evaluate preference of the type and location of various work activities. The authors observed indices of happiness of four individuals with PMD in center-based and supported work (i.e., community) experiences.…”
Section: Evaluating Activities Using Indices Of Happinessmentioning
confidence: 99%
“…32,33 With regard to the second objective, generally positive outcomes were hypothesized based on the results of (a) studies helping patients with Alzheimer's disease engage in preferred activities 34 or exercise 9 and (b) studies promoting activity engagement with persons with intellectual and multiple disabilities. 35,36 Study I-Method Participants The participants, Janice and Nancy (pseudonyms), were 58 and 79 years, respectively, and were considered to function within the moderate range of Alzheimer's disease. Their scores on the MiniMental State Examination 37 were 15 and 12, respectively.…”
mentioning
confidence: 99%
“…32,33 With regard to the second objective, generally positive outcomes were hypothesized based on the results of (a) studies helping patients with Alzheimer's disease engage in preferred activities 34 or exercise 9 and (b) studies promoting activity engagement with persons with intellectual and multiple disabilities. 35,36 Study I-Method…”
mentioning
confidence: 99%
“…In fact, Kaya and colleagues (2016) found individuals who received more vocational rehabilitation services at higher expenditure levels were more likely to obtain competitive employment. Agencies can provide a wide variety of services and training beneficial to students with significant cognitive disabilities, including job readiness training (Kaya et al, 2016), job search and placement assistance (Heal et al, 1990;Kaya et al, 2016), personal guidance assistance (Kaya et al, 2016), on-site employment coaching (Kaya et al, 2016), and community-based training in nonschool natural environments (Heal et al, 1990;Hood et al, 1996;Kaya et al, 2016;Reid et al, 1998;Wehman et al, 2014;White & Weiner, 2004). Agencies can involve supportive employers and paid and unpaid coworkers to provide authentic job training experiences (Hagner et al, 1995;Hood et al, 1996).…”
Section: Agency Assistancementioning
confidence: 99%